Analysis of Strategies for Enhancing Civil Servant Competence in Good Governance–Based Public Service Delivery in Medan Denai Subdistrict - Agung Suharyanto; Valensia Charolina Naibaho; Alya Dwi Alanti; Fanny Dalarosa Haloho; Agnes Claudia Br Lumban Gaol (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2026)
This study aims to analyze strategies to improve the competence of the State Civil Apparatus (ASN) in supporting good–governance–based public services in Medan Denai Subdistrict. The research employs a qualitative, descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving government officials at the subdistrict level who are directly engaged in public service delivery. The findings indicate that improving ASN competence is achieved through several strategies, including training and capacity development programs, periodic performance evaluations, and the use of information technology in public service systems. These strategies contribute to improving the quality of public services by making them more transparent, accountable, responsive, and efficient, in accordance with the principles of good governance. However, the implementation of these strategies still faces several challenges, including limited training budgets, variations in civil servants’ competence levels, and a suboptimal career development system for ASN. Therefore, stronger policy support and more systematic human resource management are needed to ensure sustainable improvement of ASN competence. This study highlights that the development of civil servant competence plays a crucial role in enhancing public service quality and strengthening the implementation of good governance at the subdistrict government level.